2022
DOI: 10.1097/pra.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Among Health Care Workers During the COVID-19 Pandemic

Abstract: Background: Coronavirus disease 2019 (COVID-19) has taken a significant toll on people worldwide, and in particular, on the health care workers (HCWs) who have worked on the frontlines in the fight against the pandemic. The goal of this study was to investigate the prevalence of posttraumatic stress disorder (PTSD) and related factors in HCWs in the era of COVID-19. Methods: This cross-sectional survey study was conducted between September 15, and October 15, 2020, among HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(95 reference statements)
6
9
1
Order By: Relevance
“…Of all domains under study, we found that health-related stressful experiences were consistently the ones with the strongest association with all three operationalizations of TSS in time (i.e., prevalence, incidence and persistence). This is in line with previous studies using cross-sectional study designs that found that traumatic stress was associated with fear of infecting others (Bayazit et al, 2022;Billings et al, 2021;Greene et al, 2020;Norful et al, 2021), having family members infected (Al Falasi et al, 2021;Blanco-Daza et al, 2022), stress over one's own health and feeling little control over getting infected (Annaloro et al, 2021;Blanco-Daza et al, 2022;Johnson et al, 2020;Luce ñ o-Moreno et al, 2020;Ouyang et al, 2022;Si et al, 2020). We confirm these previous findings, and our study now suggests that healthrelated stressful experiences were also associated with delayed onset as well as persistence of TSS among HCW following the first COVID-19 outbreak in Spain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of all domains under study, we found that health-related stressful experiences were consistently the ones with the strongest association with all three operationalizations of TSS in time (i.e., prevalence, incidence and persistence). This is in line with previous studies using cross-sectional study designs that found that traumatic stress was associated with fear of infecting others (Bayazit et al, 2022;Billings et al, 2021;Greene et al, 2020;Norful et al, 2021), having family members infected (Al Falasi et al, 2021;Blanco-Daza et al, 2022), stress over one's own health and feeling little control over getting infected (Annaloro et al, 2021;Blanco-Daza et al, 2022;Johnson et al, 2020;Luce ñ o-Moreno et al, 2020;Ouyang et al, 2022;Si et al, 2020). We confirm these previous findings, and our study now suggests that healthrelated stressful experiences were also associated with delayed onset as well as persistence of TSS among HCW following the first COVID-19 outbreak in Spain.…”
Section: Discussionsupporting
confidence: 92%
“…While our findings suggest that almost all of the pandemicrelated stressful experiences under study are able to provoke traumatic stress to some extent, only a few were predictive of TSS persistence. The risk factor with the highest association with persisting TSS in our study was having patient(s) who died from COVID, in line with previous cross-sectional findings (Bayazit et al, 2022;Leng et al, 2021;Lockett et al, 2022). Interestingly, this was also the only stressful experience under study considered consistent with DSM-5 criterion A of PTSD and the only one consistently associated with TSS persistence in all analyses (i.e., even after additionally adjusting for co-occurring depression and anxiety).…”
Section: Discussionsupporting
confidence: 90%
“…They were worried about getting infected with COVID-19, spreading COVID-19 to the people they live with, financial problems, losing connection with their family and loved ones, and the feeling of overwhelmed at work. These negative feelings were similar to the findings in previous reports 39 , 40 and have been also widely reported in past epidemics such as HIV and SARS. 41 , 42 We also found that having more concerns and having higher degree of fear were independently associated with more severe PTSD.…”
Section: Discussionsupporting
confidence: 91%
“…Based on such premises, the COMET study was the first trial evaluating the global impact of the COVID-19 pandemic and its related containment measures on mental health and well-being in a wide sample of the Italian population (Giallonardo et al, 2020). Specifically, the purpose of the present study was to investigate how the lockdown Bayazit et al, 2022;Schou-Bredal et al, 2022;Baker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%